Clinical Significance and Immunologic Landscape of a Five-IL(R)-Based Signature in Lung Adenocarcinoma - Fan, Tao; Pan, Shize; Yang, Shuo; Hao, Bo; Zhang, Lin; Li, Donghang; Geng, Qing (Frontiers in Immunology, 2021)
The interleukin (IL) family plays important roles in the anti-tumor immune response. However, the expression signature and clinical characteristics of the IL family in lung adenocarcinoma (LUAD) remains unclear. The main purpose of this study is to explore the expression profile of IL family genes and construct an IL family-based prognostic signature in LUAD. Five public datasets of 1312 patients with LUAD were enrolled in this study. Samples from The Cancer Genome Atlas (TCGA) were used as the training set, and samples from the other four cohorts extracted from Gene Expression Omnibus (GEO) database were used as the validation set. Additionally, the profile of IL family signature was explored and the association between this signature and immunotherapy response was also analyzed. Meanwhile, the prognostic value was compared between this IL-based signature and different immunotherapy markers. A signature based on five identified ILs was constructed using the TCGA dataset through univariate / multivariable Cox proportional hazards regression and LASSO Cox analysis. These cases with LUAD were stratified into high-risk and low-risk group according to the risk score. This signature showed a strong predictive ability, which was verified by the five independent cohorts and clinical subtypes. The IL-based models presented unique characteristics in terms of immune cell infiltration and immune inflammation profile in tumor microenvironment (TME). Biological pathway analysis confirmed that high-risk patients showed significant T-cell and B-cell immunosuppression, and rapid tumor cell proliferation. More importantly, we researched the relationship between this IL-based signature and immune checkpoints, tumor mutation burden (TMB), tumor purity and ploidy, and TIDE score, which confirmed this signature gave the best predictive value. We first provided a robust prognostic IL-based signature, which had a potential as a predictor for immunotherapy response to realize individualized treatment of LUAD.